Quantum Chemical and Biological Properties of Coumarin Derivative Compound - Saraç, Kamuran; Çetin, Burcu (Niyazi BULUT, 2023)
This work presents the characterization of 8-t-buthyl-4-methyl-2H- chromen 2-one by quantum chemical calculations and spectral techniques. The molecular geometry, vibrational frequencies and gauge including atomic orbital (GIAO) 1H and 13C NMR chemical shift values of title compound in the ground state have been calculated using the density functional method (B3LYP) with the 6-31G(d) basis set. The theoretical vibrational frequencies and chemical shift values show good agreement with experimental values. In addition, DFT calculations of molecular electrostatic potentials and frontier molecular orbitals of the title were carried out at the B3LYP/6-31G(d) level of theory. The title compound was screened for antibacterial, antifungal and antioxidant activities.
Keywords: Classical Physics (Other); Klasik Fizik (Diğer)